2002
DOI: 10.1017/s1357729800052723
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the voluntary intake and digestibility of buffel-grass and lucerne hays offered to Brahman-cross cattle using n-alkanes

Abstract: The n-alkane method was developed in temperate areas as a tool to estimate voluntary intake (VI) at pasture. The present study aimed to investigate the performance of n-alkanes as markers for estimating VI of steers (mean live weight 213 kg) offered a range of tropical grass hays and lucerne. Tropical and temperate forages have different n-alkane profiles and little is known about the issues which affect the accuracy of the method under tropical conditions. In two pen experiments (no. = 20 and no. = 24) n-alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
25
0
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 10 publications
10
25
0
8
Order By: Relevance
“…Some studies have indicated that faecal alkane recoveries are unaffected by diet (Mayes et al, 1986;Brosh et al, 2003) or feeding level (Mayes et al, 1986;Dove et al, 1989;Dove and Olivá n, 1998;Elwert et al, 2004); whereas others reported that alkane recoveries were influenced by diet types (Dove et al, 1989;Hendricksen et al, 2002;Ferreira et al, 2005 and, feeding level (Dillon, 1993;Dove et al, 2002) or herbage species (Lin et al, 2007;Elwert et al, 2008). To date, little published data are available evaluating the effects of herbage species and live weight on faecal alcohol and acid recoveries.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that faecal alkane recoveries are unaffected by diet (Mayes et al, 1986;Brosh et al, 2003) or feeding level (Mayes et al, 1986;Dove et al, 1989;Dove and Olivá n, 1998;Elwert et al, 2004); whereas others reported that alkane recoveries were influenced by diet types (Dove et al, 1989;Hendricksen et al, 2002;Ferreira et al, 2005 and, feeding level (Dillon, 1993;Dove et al, 2002) or herbage species (Lin et al, 2007;Elwert et al, 2008). To date, little published data are available evaluating the effects of herbage species and live weight on faecal alcohol and acid recoveries.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few direct comparisons of faecal marker recoveries from various herbage species exist, most of these studies came to the similar conclusion. In cattle, differences of faecal alkane recoveries were observed between herbage species (Ohajuruka and Palmquist, 1991;Hendricksen et al, 2002). In sheep, recent studies found an effect of herbage species on faecal recoveries of alkanes (Lin et al, 2007;Elwert et al, 2008), alcohols and acids (Lin et al, 2009a).…”
Section: Faecal Recoveries Of Alkanes Alcohols and Acidsmentioning
confidence: 99%
“…Moreover, in the present experiment, concentrations of C 31 and C 33 in plant materials were low, which could also have increased the variation associated with DM intake estimates. Using the alkane C 35 to C 36 ratio, Hendricksen et al (2002) reported that estimation of DM intake was more variable when herbage alkane content was less than 20 mg kg -1 for an alfalfa-based diet. Estimation of intake using the double alkanes technique has been shown to be generally satisfactory in sheep (Dove et Mayes 1985Vulich et al 1991;Dove et al 2002), but results with cattle are more variable (Dillon and Stakelum 1989;Berry et al 2000;Hendricksen et al 2002;Charmley et al 2003), suggesting that additional research is required in the bovine.…”
Section: Dry Matter Intakementioning
confidence: 99%